Study of Pruning Types and Liquid Organic Fertilizer Concentration on Growth and Yield of Pepper (Capsicum frutescens L.) - Ramdan Hidayat; Widi Wurjani (Nusantara Science and Technology Proceedings, 2022)
This study aims to determine the best of combination treatment of pruning type and concentration of liquid organic fertilizer (LOF) on the growth and yield of pepper plants whose production is still low and has not yet achieved its production potential which can reach 20 tons/ha. The factorial study with 2 factors was arranged in a completely randomized design (CRD) which was repeated 3 times. The first factor is the type of pruning (P) which consists of 3 levels, namely: P0 = Not pruned (control), P1 = Pruning shoot tip, P2 = Pruning axillary shoot, while the second factor is the concentration of LOF NASA which consists of 3 levels , namely: K0 = 0 ml/l (control), K1 = 2 ml/l, and K2 = 4 ml/l. The results showed that there was a significant interaction between the combination of shoot pruning treatment and LOF NASA concentration on the number of branches and the number of productive branches. The combination of shoot trimming treatment and LOF NASA concentration of 2 ml/l water (P1K1) resulted in the best growth of pepper. Meanwhile, the single factor type of shoot tip pruning (P1) and LOF NASA concentration of 2 ml/l (K1) produced the best number of fruits and fruit weight of papper compared to other treatments.